Dimensions of Desire Strength - Federico Burdman (Daimon)
The question I address in this paper is what is it exactly for desires to possess a certain strength. And my aim is twofold. First, I argue for a pluralistic account of desire strength. On this view, there are several dimensions along which desires possess greater or lesser strength, and none of them is intrinsically privileged. My second aim is to highlight some time-based properties of desires, recurrence and persistence. Both desires’ degree of persistence across time and their rate of episodic recurrence are, I argue, further dimensions of desire strength.